Resilience of bumblebee foraging behavior despite colony size reduction - Gérard, Maxence; Marchand, Justine; Zanutto, Jade; Baird, Emily (Frontiers in Insect Science, 2023)
Foraging behavior is driven by diverse factors, notably life history traits. Foraging strategies are particularly complex among eusocial species such as bumblebees, because they depend primarily on the needs of the colony, rather than on individual’s needs. Colony size, i.e. the number of workers in a colony vary a lot among eusocial insects. While a large colony can be adaptive, several drivers can strongly decrease colony size, like pesticides or high temperatures. In this study, we used the bumblebee Bombus terrestris to assess if workers adapted their foraging behavior to such rapid decreases in colony size. We conducted the foraging experiments with two plant species commonly used by bumblebees: Borago officinalis and Echium plantagineum. Several foraging parameters were measured: foraging time, number of foraging trips, number of workers foraging, visiting time and visiting rate. Despite a drastic reduction in colony size, nearly all the foraging behavior parameters were unaffected by the colony size reduction. Colonies that were subject to a large decrease in workers instead displayed high resilience and behavioral plasticity by quickly increasing the proportion of foragers. Ultimately, further researches should assess if this consistency in foraging behavior also allows bumblebee colonies to maintain both the efficiency of the resources collection and pollination.